Bacterial and fungal community differentiation in microhabitats created by Lumbricus and Aporrectodea anecic earthworm species - Kevin Hoeffner; Daniel Cluzeau; Julien Tremblay; Mathieu Santonja; Cécile Monard (Applied Soil Ecology, 2026)

Ecosystem Synchrony Among Small Shallow Lakes is Driven Differently by Their Biotic and Abiotic Similarities - Chloé Vagnon; Mathieu Chevalier; Stéphanie Boulêtreau; Flavien Garcia; Julian D. Olden; Julien Cucherousset (Ecosystems, 2026)
Identifying the coordinated responses and the biotic and abiotic drivers of aquatic ecosystem dynamics across space and time is the key to understanding and predicting ecosystem trajectories under global change. Here, we applied the concept of ecosystem synchrony (that is, similarities in temporal fluctuations of ecosystem functions across space) to evaluate: (1) the coordinated dynamics of 16 French gravel pit lakes and (2) how geographic proximity, abiotic and biotic similarities explain their level of synchrony. We quantified both multi-year (two-year period) and seasonal (warm vs. cold seasons) levels of synchrony in dissolved oxygen saturation using high-frequency (10 min) measurements. We showed that the two-year ecosystem synchrony was driven by the environmental similarities in abiotic (for example, nutrient levels, hydromorphology) and biotic (for example, fish biomass) conditions between lakes yet the relative influence of these two processes varied seasonally. Indeed, ecosystem synchrony during warm seasons was primarily driven by abiotic environmental conditions, likely reflecting the stronger control of physical and chemical conditions on ecosystem functioning. Conversely, biotic similarity was more influential on ecosystem synchrony during cold seasons, suggesting a greater influence of biological structure under reduced ecosystem productivity. Geographic distance had a negligible effect, likely due to the relatively limited spatial extent of the lake network. These findings highlight the value of ecosystem synchrony as a spatiotemporal integrator of ecosystem dynamics and emphasize the need to account for both the temporal scale and local biotic and abiotic context dependencies when assessing the ecological trajectories of ecosystems.

Leaf litter chemistry contributes to shape the chemical footprint of macrodetritivore communities - Théo Marchand; Matthieu Chauvat; Estelle Forey; Florence Maunoury-Danger; Mathieu Santonja; Michaël Danger; Philippe Usseglio-Polatera; David Baqué; Frédéric Candaudap; Sophia V. Hansson; Frédéric Julien; Christophe Laplanche; et al. (Applied Soil Ecology, 2026)

Blood flow restriction exacerbates muscle deoxygenation and fatigue during sport climbing specific finger flexors resistance training - Titouan P. Perrin; Hugo Randy; Xavier Hugues; Nicolas Tourette; Marie Coudurier; Michel Guinot; Violaine Cahouet; Franck Quaine; Stéphane Doutreleau; Hugo A. Kerherve; Mathieu Marillier; Julien V. Brugniaux (European Journal of Applied Physiology, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Integration of the exposome concept into health risk assessments: a challenge for health safety agencies - Amélie Crépet; Philippe Quénel; Jeanne Garric; Alain Kaufmann; Jean-Marc Bonmatin; Pascale Duché; Aurélie Mathieu; Madeline Carsique; Julien Jean; Pascal Sanders; Jean-Pierre Cravedi; Matthieu Schuler; et al. (Environmental Research, 2025)

Experimental Evidence for the Desynchronization of Ecosystem Dynamics by Global Change - Chloé Vagnon; Mathieu Chevalier; Stéphanie Boulêtreau; Rosalie Bruel; Sophie Guillon; Gordon Holtgrieve; Michelle Jackson; Julian D. Olden; Valentin Marin; Alexis Millot; Elisa Thebault; Pablo A. Tedesco; et al. (Ecology Letters, 2025)
Anticipating ecosystem responses to global change requires identifying the isolated and combined effects of environmental disturbance across both space and time. Examining the coordinated responses of ecosystems has recently emerged as a powerful approach to advance this understanding. We conducted two complementary experiments to identify whether, and if so how, warming temperatures, nutrient enrichment, predator overexploitation (i.e., reduced apex predator abundance) and their combination drive coordinated responses of freshwater ecosystems by evaluating the dynamics of synchrony between control and disturbed mesocosms using high‐frequency dissolved oxygen saturation measurements, an integrative parameter of the metabolic balance of ecosystems. Nutrient enrichment desynchronized the oxygen dynamics and their component cycles between treatments, likely arising from elevated primary production. Warming and overexploitation tended to desynchronize oxygen cycles from the control, particularly at short time scales. Nutrient enrichment combined with warming dampened desynchronization between control (ambient) and treatment mesocosms, whereas desynchronization was enhanced when simultaneously subject to predator overexploitation. As one of the first experimental demonstrations of global change impacts on ecosystem synchrony, this study highlights the need—and opens new avenues—to detect alterations in ecosystem functioning across previously unexplored spatial and temporal scales.

Geochemical investigations of metal bioaccumulation in oysters along the land-sea continuum: Sources, fluxes and reactivity in the Seudre Estuary (France) - Jean Rillard; Julien Mathieu; Loïc Lalague; Anne Marie Desaulty; Jean Philippe David (Science of The Total Environment, 2025)

Bridging lab and field: Tracking environmentally relevant nanoplastics in crops using Py-GC/MS - Nataliia Ryzhenko; Guillaume Pecheul; Aline Dia; Lionel Dutruch; Maxime Pattier; Mathieu Pédrot; Julien Gigault; Mélanie Davranche (Journal of Hazardous Materials, 2025)

Management of invasive candidiasis in French ICUs: insights from a 2024 nationwide survey - Mathieu Esposito; Florent Lemery; Nelly Agrinier; Marc Soudant; Alexandre Charmillon; Nicolas Degand; Joséphine Dorin; Jean Dellamonica; Lucas Morand; Claire Roger; Julien Scala-Bertola; Marc Leone; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Local, environmental and trace metal effects on gut microbiota diversity in urban feral pigeons - Clarence Schmitt; Julien Gasparini; Héloïse Moullec; Laurence Walch; Mathieu Leroux-Coyau; Julie Leloup (Environmental Research, 2025)

Benthic macroinvertebrate diversity and function in an agricultural constructed wetland affected by agrochemical pressure (Seine-et-Marne, France) - Alexandre Michel; Jérémie D. Lebrun; Cédric Chaumont; Mathieu Girondin; Julien Tournebize; Virginie Archaimbault; Alienor Jeliazkov (Environmental Science and Pollution Research, 2025)

No experimental evidence of an adaptive antioxidative response induced by trace metals exposure in feral pigeons - Clarence Schmitt; Louise Cavaud; Héloïse Moullec; Mathieu Leroux-Coyau; Laurence Walch; Julien Gasparini (Journal of Ornithology, 2025)

Social information use for spatial decision in the common lizard, Zootoca vivipara - Mathieu Brevet; Staffan Jacob; Alexis Rutschmann; Murielle Richard; Julien Cote; Jean Clobert (Animal Behaviour, 2024)

Ecosystem synchrony: an emerging property to elucidate ecosystem responses to global change - Chloé Vagnon; Julian D. Olden; Stéphanie Boulêtreau; Rosalie Bruel; Mathieu Chevalier; Flavien Garcia; Gordon Holtgrieve; Michelle Jackson; Elisa Thebault; Pablo A. Tedesco; Julien Cucherousset (Trends in Ecology & Evolution, 2024)

Fate of chlordecone in soil food webs in a banana agroecosystem in Martinique - Mathieu Coulis; Julie Senecal; Yoann Devriendt-Renault; Thierry Guerin; Julien Parinet; Lai Ting Pak (Environmental Pollution, 2024)

Unravelling the magmatic and hydrothermal evolution of rare-metal granites through apatite geochemistry and geochronology: The Variscan Beauvoir granite (French Massif Central) - Océane Rocher; Christophe Ballouard; Antonin Richard; Loïs Monnier; Patrick Carr; Oscar Laurent; Yanis Khebabza; Andreï Lecomte; Nordine Bouden; Johan Villeneuve; Benjamin Barré; Patrick Fullenwarth; et al. (Chemical Geology, 2024)

From planning to implementation: a multi-stakeholder partnership for managing plant invasions in tropical island ecosystems - Mathieu Rouget; Pauline Fenouillas; Emilie Cazal; Margot Caubit; Cédric Ajaguin Soleyen; Eve Balard; Antoine Becker-Scarpitta; Laurent Calichiama; Gael Karczewski; Christophe Lavergne; Benoît Lequette; Roxane L’Horset; et al. (Biological Invasions, 2024)

Evaluating the impact of climate change and millennial variability on the last Neanderthal populations in Europe (Marine Isotope Stage 3) - Benjamin Albouy; Simon Paquin; Julien Riel-Salvatore; Masa Kageyama; Mathieu Vrac; Ariane Burke (Quaternary Science Reviews, 2024)

Do nanoplastics impact Pb up-taking by Hordeum vulgare L.? - Nataliia Ryzhenko; Lionel Dutruch; Briscine Tabo; Guillaume Pecheul; Maxime Pattier; Imane Khatib; Mathieu Pédrot; Julien Gigault; Francisco Cabello-Hurtado; Abdelhak El Amrani; Mélanie Davranche (NanoImpact, 2024)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Space use of invertebrates in terrestrial habitats: Phylogenetic, functional and environmental drivers of interspecific variations - Gwenaëlle Auger; Julien Pottier; Jérôme Mathieu; Franck Jabot (Global Ecology and Biogeography, 2024)
Aim We present the first global database of movement patterns of terrestrial invertebrates, focusing on active dispersal and foraging movements. We depict interspecific variations in movement distances among invertebrates and assess potential drivers of these variations. We finally contrast our results with those of previous vertebrate studies. Location Worldwide. Methods We conducted a meta‐analysis using 176 studies. They provided 411 movement estimates: 175 foraging movement estimates for 101 species, 51 families and 19 orders, and 236 dispersal estimates for 131 species, 53 families and 16 orders. These estimates were complemented by several organism functional traits: body mass, diet, locomotion mode and by environmental variables of the study sites: temperature and NDVI. We computed allometric relationships between movement distances and body mass both globally and separately for each taxonomic order with sufficient data. We tested the relative influence of the co‐variables on movement distances through model selection. Results We reveal a general positive allometric relationship between movement distance and body mass that holds across most taxonomic orders. We evidence a strong phylogenetic signal in movement distances that translates in variable allometries of movement distances with body mass across taxonomic orders. We further find that interspecific variations of movement distances are primarily correlated with functional differences rather than environmental conditions. Locomotion mode is the most important explanatory variable of both dispersal and foraging distances, with larger distances among flying individuals followed by walking and crawling ones for a given body mass. Surprisingly, trophic guild has a low predictive power of invertebrate movement distances as opposed to vertebrates, with unclear differences between invertebrate carnivores, herbivores and decomposers. Main Conclusions Our study provides general allometric equations for terrestrial movement distances of invertebrates. It further reveals important functional drivers of their interspecific variation in space use with a dominant role of their evolutionary history.

Mixture effects of pharmaceuticals carbamazepine, diclofenac and venlafaxine on Mytilus galloprovincialis mussel probed by metabolomics and proteogenomics combined approach - Thibaut Dumas; Elena Gomez; Julien Boccard; Gaëlle Ramirez; Jean Armengaud; Aurélie Escande; Olivier Mathieu; Hélène Fenet; Frédérique Courant (Science of The Total Environment, 2024)

Condition of composted microplastics after they have been buried for 30 years: Vertical distribution in the soil and degree of degradation - Aurélie Wahl; Mélanie Davranche; Murielle Rabiller-Baudry; Mathieu Pédrot; Imane Khatib; Fabian Labonne; Marion Canté; Candice Cuisinier; Julien Gigault (Journal of Hazardous Materials, 2024)

Evolution of the alpine Critical Zone since the Last Glacial Period using Li isotopes from lake sediments - Xu (Yvon) Zhang; Manon Bajard; Julien Bouchez; Pierre Sabatier; Jérôme Poulenard; Fabien Arnaud; Christian Crouzet; Marie Kuessner; Mathieu Dellinger; Jérôme Gaillardet (Earth and Planetary Science Letters, 2023)

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Combined use of 87Sr/86Sr and carbon isotopes with multielemental analysis for the geographical authentication of Tunisian and European olive oils - Emna G. Nasr; Ekaterina N. Epova; Julien Barre; Mathieu Sebilo; Alberto de Diego; Radhia Souissi; Houyem Abderrazak; Olivier F.X. Donard (Food Chemistry, 2023)

Are nanoplastics potentially toxic for plants and rhizobiota? Current knowledge and recommendations - Delphine Masson; Mathieu Pédrot; Mélanie Davranche; Francisco Cabello-Hurtado; Nataliia Ryzhenko; Abdelhak El Amrani; Aurélie Wahl; Julien Gigault (NanoImpact, 2023)

Titanium transport and isotopic fractionation in the Critical Zone - Sarah M. Aarons; Nicolas Dauphas; Nicolas D. Greber; Mathieu Roskosz; Julien Bouchez; Tamara Carley; Xiao-Ming Liu; Roberta L. Rudnick; Jérôme Gaillardet (Geochimica et Cosmochimica Acta, 2023)

Intraseasonal descriptors and extremes in South African rainfall. Part II : Summer teleconnections across multiple timescales - Asmat Ullah; Benjamin Pohl; Julien Pergaud; Bastien Dieppois; Mathieu Rouault (International Journal of Climatology, 2023)
Extreme events contribute significantly to rainfall variability in semi‐arid regions like South Africa. Here, following the definition of a novel typology of rainfall extremes, disentangling large‐ and small‐scale events in Part I, we use quality‐controlled observational databases in South Africa, the ERA5 reanalysis and satellite estimates TRMM‐3B42 to examine the relationship between these two types of rainfall extremes and different modes of climate variability at various timescales. At low frequencies, rainfall extremes are assessed at interannual (IV: 2–8 years) and quasi‐decadal (QDV: 8–13 years) timescales, which are primarily associated with the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), respectively. At subseasonal timescales, the typology of rainfall extremes is analysed depending on the synoptic configurations, as inferred by seven convective regimes including tropical temperate troughs (TTTs: 3–7 days), and the intraseasonal variability associated with the Madden–Julien Oscillation (MJO: 30–60 days). At the IV timescale, the occurrence of large‐scale extremes is substantially higher during its wet phases thereby suggesting a 400% rise in the occurrence of large‐scale extremes as compared to its dry phases. At the QDV timescale, variability mostly relates to the modulation of small‐scale extremes during its wet phases. Teleconnections with global sea surface temperature (SST) confirm that La Niña conditions favour overall wet conditions and extremes in South Africa. The numbers of large‐scale extremes are consistently related to warmer SSTs in the North Atlantic, while their link with warmer Indian and tropical South Atlantic oceans is found to be statistically independent of the state of ENSO. At the subseasonal timescales, large‐scale extremes largely occur during three out of the seven convective regimes identified in the southern African region whereas small‐scale extremes are nearly equiprobable during all convective regimes. The occurrence of large‐scale extremes during continent‐rooted TTT is further enhanced during the locally wet phases of the MJO and is symmetrically weakened during its dry phases.

Physical processes and biological productivity in the upwelling regions of the tropical Atlantic - Peter Brandt; Gaël Alory; Founi Mesmin Awo; Marcus Dengler; Sandrine Djakouré; Rodrigue Anicet Imbol Koungue; Julien Jouanno; Mareike Körner; Marisa Roch; Mathieu Rouault (Ocean Science, 2023)
In this paper, we review observational and modelling results on the upwelling in the tropical Atlantic between 10∘ N and 20∘ S. We focus on the physical processes that drive the seasonal variability of surface cooling and the upward nutrient flux required to explain the seasonality of biological productivity. We separately consider the equatorial upwelling system, the coastal upwelling system of the Gulf of Guinea and the tropical Angolan upwelling system. All three tropical Atlantic upwelling systems have in common a strong seasonal cycle, with peak biological productivity during boreal summer. However, the physical processes driving the upwelling vary between the three systems. For the equatorial regime, we discuss the wind forcing of upwelling velocity and turbulent mixing, as well as the underlying dynamics responsible for thermocline movements and current structure. The coastal upwelling system in the Gulf of Guinea is located along its northern boundary and is driven by both local and remote forcing. Particular emphasis is placed on the Guinea Current, its separation from the coast and the shape of the coastline. For the tropical Angolan upwelling, we show that this system is not driven by local winds but instead results from the combined effect of coastally trapped waves, surface heat and freshwater fluxes, and turbulent mixing. Finally, we review recent changes in the upwelling systems associated with climate variability and global warming and address possible responses of upwelling systems in future scenarios.

Generic method to assess transmutation feasibility for nuclear waste treatment and application to irradiated graphite - Mathieu Rasson; Julien Fuchs; Grégoire Augé; Jean-Louis Quéri; Gérard Laurent (Annals of Nuclear Energy, 2023)

A research-action process to implement priority areas for alien plant clearing on Reunion Island - Pauline Fenouillas; Claudine Ah-Peng; Elise Amy; Isabelle Bracco; Laurent Calichiama; Emilie Cazal; Mélodie Gosset; Florent Ingrassia; Christophe Lavergne; Benoit Lequette; Jean-Cyrille Notter; Jean-Marie Pausé; et al. (Biological Invasions, 2023)

An innovative mechanical model for structural steel joints - Tudor Golea; Adrien Corman; Julien Mathieu; Yves Duchêne; Jean-Pierre Jaspart; Jean-François Demonceau (Engineering Structures, 2023)

The role of vital dietary biomolecules in eco-evo-devo dynamics - Libor Závorka; Andreu Blanco; Fernando Chaguaceda; Julien Cucherousset; Shaun S. Killen; Camilla Liénart; Margaux Mathieu-Resuge; Pavel Němec; Matthias Pilecky; Kristin Scharnweber; Cornelia W. Twining; Martin J. Kainz (Trends in Ecology & Evolution, 2023)

Long-term exposure to nitrogen dioxide air pollution and breast cancer risk: A nested case-control within the French E3N cohort study - Amina Amadou; Delphine Praud; Thomas Coudon; Floriane Deygas; Lény Grassot; Mathieu Dubuis; Elodie Faure; Florian Couvidat; Julien Caudeville; Bertrand Bessagnet; Pietro Salizzoni; Karen Leffondré; et al. (Environmental Pollution, 2023)

Intraseasonal descriptors and extremes in South African rainfall. Part I: Summer climatology and statistical characteristics - Asmat Ullah; Benjamin Pohl; Julien Pergaud; Bastien Dieppois; Mathieu Rouault (International Journal of Climatology, 2022)
Rainfall extremes are of major and increasing importance in semi‐arid countries and their variability has strong implications for water resource and climate impacts on the local societies and environment. Here, we examine intraseasonal descriptors (ISDs) and wet extremes in austral summer rainfall (November–February) over South Africa (SA). Using daily observations from 225 rain gauges and ERA5 reanalysis between 1979 and 2015, we propose a novel typology of wet extreme events based on their spatial fraction, thus differentiating large‐ and small‐scale extremes. Long‐term variability of both types of extreme rainfall events is then extensively discussed in the context of ISDs. The results demonstrate that using 7% of spatial fraction simultaneously exceeding the local threshold of the 90th percentile produces remarkable results in characterizing rainfall extremes into large‐ and small‐scale extremes. Austral summer total rainfall is found to be primarily shaped by large‐scale extremes which constitute more than half of the rainfall amount under observation, and nearly half in ERA5. Observation (ERA5) shows an average of 8 ± 5 (20 ± 7) days per season associated with large‐scale extremes, which are comprised in 5 ± 3 (10 ± 3) spells with an average persistence of at least 2 days. Overall, we find a strong dependence of total rainfall on the number of wet days and wet spells that are associated with large‐scale extremes. We also find that large‐ and small‐scale extremes are well‐organized and spatially coherent in nature yet extreme conditions during small‐scale events are found sporadic over the region, contrasting with large‐scale events for which extreme conditions are found over a larger and coherent region.

The time course of different neuromuscular adaptations to short-term downhill running training and their specific relationships with strength gains - Bastien Bontemps; Mathieu Gruet; Julien Louis; Daniel J. Owens; Stella Miríc; Robert M. Erskine; Fabrice Vercruyssen (European Journal of Applied Physiology, 2022)
Purpose Due to its eccentric nature, downhill running (DR) training has been suggested to promote strength gains through neuromuscular adaptations. However, it is unknown whether short-term chronic DR can elicit such adaptations. Methods Twelve untrained, young, healthy adults (5 women, 7 men) took part in 4 weeks’ DR, comprising 10 sessions, with running speed equivalent to 60–65% maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max , assessed at weeks 0 and 4). Isometric and isokinetic knee-extensor maximal voluntary torque (MVT), vastus lateralis (VL) muscle morphology/architecture (anatomical cross-sectional area, ACSA; physiological CSA, PCSA; volume; fascicle length, L f ; pennation angle, PA) and neuromuscular activation (VL EMG) were assessed at weeks 0, 2 and 4. Results MVT increased by 9.7–15.2% after 4 weeks ( p < 0.01). VL EMG during isometric MVT increased by 35.6 ± 46.1% after 4 weeks ( p < 0.05) and correlated with changes in isometric MVT after 2 weeks ( r = 0.86, p = 0.001). VL ACSA (+2.9 ± 2.7% and +7.1 ± 3.5%) and volume (+2.5 ± 2.5% and +6.6 ± 3.2%) increased after 2 and 4 weeks, respectively ( p < 0.05). PCSA (+3.8 ± 3.3%), PA (+5.8 ± 3.8%) and L f (+2.7 ± 2.2%) increased after 4 weeks ( p < 0.01). Changes in VL volume ( r = 0.67, p = 0.03) and PCSA ( r = 0.71, p = 0.01) correlated with changes in concentric MVT from 2 to 4 weeks. $$\dot{V}$$ V ˙ O 2max (49.4 ± 6.2 vs. 49.7 ± 6.3 mL·kg −1 ·min −1 ) did not change after 4 weeks ( p = 0.73). Conclusion Just 4 weeks’ moderate-intensity DR promoted neuromuscular adaptations in young, healthy adults, typically observed after high-intensity eccentric resistance training. Neural adaptations appeared to contribute to most of the strength gains at 2 and 4 weeks, while muscle hypertrophy seemed to contribute to MVT changes from 2 to 4 weeks only.

Growth‐enhanced salmon modify stream ecosystem functioning - Julien Cucherousset; Line E. Sundt‐Hansen; Mathieu Buoro; Libor Závorka; Rémy Lassus; Knut A. E. Bækkelie; Ian A. Fleming; Björn Thrandur Björnsson; Jörgen I. Johnsson; Kjetil Hindar (Journal of Fish Biology, 2021)
Use of fast‐growing domesticated and/or genetically modified strains of fish is becoming increasingly common in aquaculture, increasing the likelihood of deliberate or accidental introductions into the wild. To date, their ecological impacts on ecosystems remain to be quantified. Here, using a controlled phenotype manipulation by implanting growth hormone in juvenile Atlantic salmon ( Salmo salar ), we found that growth‐enhanced fish display changes in several phenotypic traits known to be important for ecosystem functioning, such as habitat use, morphology and excretion rate. Furthermore, these phenotypic changes were associated with significant impacts on the invertebrate community and key stream ecosystem functions such as primary production and leaf‐litter decomposition. These findings provide novel evidence that introductions of growth‐enhanced fish into the wild can affect the functioning of natural ecosystems and represent a form of intraspecific invasion. Consequently, environmental impact assessments of growth‐enhanced organisms need to explicitly consider ecosystem‐level effects.

Growth resistance and resilience of mixed silver fir and Norway spruce forests in central Europe: Contrasting responses to mild and severe droughts - Alessandra Bottero; David I. Forrester; Maxime Cailleret; Ulrich Kohnle; Arthur Gessler; Dominic Michel; Arun K. Bose; Jürgen Bauhus; Harald Bugmann; Matthias Cuntz; Loïc Gillerot; Marc Hanewinkel; et al. (Global Change Biology, 2021)
Extreme droughts are expected to increase in frequency and severity in many regions of the world, threatening multiple ecosystem services provided by forests. Effective strategies to adapt forests to such droughts require comprehensive information on the effects and importance of the factors influencing forest resistance and resilience. We used a unique combination of inventory and dendrochronological data from a long‐term (>30 years) silvicultural experiment in mixed silver fir and Norway spruce mountain forests along a temperature and precipitation gradient in southwestern Germany. We aimed at examining the mechanisms and forest stand characteristics underpinning the resistance and resilience to past mild and severe droughts. We found that (i) fir benefited from mild droughts and showed higher resistance (i.e., lower growth loss during drought) and resilience (i.e., faster return to pre‐drought growth levels) than spruce to all droughts; (ii) species identity determined mild drought responses while species interactions and management‐related factors strongly influenced the responses to severe droughts; (iii) intraspecific and interspecific interactions had contrasting effects on the two species, with spruce being less resistant to severe droughts when exposed to interaction with fir and beech; (iv) higher values of residual stand basal area following thinning were associated with lower resistance and resilience to severe droughts; and (v) larger trees were resilient to mild drought events but highly vulnerable to severe droughts. Our study provides an analytical approach for examining the effects of different factors on individual tree‐ and stand‐level drought response. The forests investigated here were to a certain extent resilient to mild droughts, and even benefited from such conditions, but were strongly affected by severe droughts. Lastly, negative effects of severe droughts can be reduced through modifying species composition, tree size distribution and stand density in mixed silver fir‐Norway spruce forests.

Quantitative estimates of freshwater fish stocking practices by recreational angling clubs in France - Julien Cucherousset; Rémy Lassus; Carsten Riepe; Paul Millet; Frédéric Santoul; Robert Arlinghaus; Mathieu Buoro (Fisheries Management and Ecology, 2021)
Although freshwater fish stocking is widely used by managers, quantitative assessments of stocking practices are lacking in many countries. The general objective of the present study was to determine the quantity and characteristics of fish stocking in metropolitan France. Using a survey‐based approach, stocking practices for 2013 by recreational angling clubs in France were quantified, which represented the bulk of fish stocking undertaken in that year. Stocking was found to be practiced by 88.6% of angling clubs in France, representing, on average, 65% of their annual budget. Overall, 22 species were stocked, including 13 native and nine non‐native species, with strong variations among species in terms of life stages and body sizes used for stocking. Using Bayesian modelling, a total biomass of 2.029 t, representing approximately 90 million fishes, was estimated to be stocked in France in 2013. In terms of biomass, the most widely stocked species were rainbow trout Oncorhynchus mykiss (Walbaum), brown trout Salmo trutta L., roach Rutilus rutilus (L.), common carp Cyprinus carpio L. and northern pike Esox lucius L. A stocking volume of approximately 60 fishes or 1.5 kg of fish biomass per angler per year seems commonplace in industrialised countries for which data are available.

Impact of whole genome triplication on the evolutionary history and the functional dynamics of regulatory genes involved in Brassica self-incompatibility signalling pathway - Thanina Azibi; Houria Hadj-Arab; Maryse Lodé; Julie Ferreira de Carvalho; Gwenn Trotoux; Sylvie Nègre; Marie-Madeleine Gilet; Julien Boutte; Jérémy Lucas; Xavier Vekemans; Anne-Marie Chèvre; Mathieu Rousseau-Gueutin (Plant Reproduction, 2020)

Southern African summer-rainfall variability, and its teleconnections, on interannual to interdecadal timescales in CMIP5 models - Bastien Dieppois; Benjamin Pohl; Julien Crétat; Jonathan Eden; Moussa Sidibe; Mark New; Mathieu Rouault; Damian Lawler (Climate Dynamics, 2019)

Sharing cells with Wolbachia : the transovarian vertical transmission of Culex pipiens densovirus - Mine Altinli; Julien Soms; Marc Ravallec; Fabienne Justy; Manon Bonneau; Mylene Weill; Anne‐Sophie Gosselin‐Grenet; Mathieu Sicard (Environmental Microbiology, 2019)
Summary Culex pipiens densovirus (CpDV), a single stranded DNA virus, has been isolated from Culex pipiens mosquitoes but differs from other mosquito densoviruses in terms of genome structure and sequence identity. Its transmission from host to host, the nature of its interactions with both its host and host's endosymbiotic bacteria Wolbachia are not known. Here, we report the presence of CpDV in the ovaries and eggs of Cx. pipiens mosquitoes in close encounters with Wolbachia . In the ovaries, CpDV amount significantly differed between mosquito lines harbouring different strains of Wolbachia and these differences were not linked to variations in Wolbachia densities. CpDV was vertically transmitted in all laboratory lines to 17%–20% of the offspring. For some females, however, the vertical transmission reached 90%. Antibiotic treatment that cured the host from Wolbachia significantly decreased both CpDV quantity and vertical transmission suggesting an impact of host microbiota, including Wolbachia, on CpDV transmission. Overall our results show that CpDV is transmitted vertically via transovarian path along with Wolbachia with which it shares the same cells. Our results are primordial to understand the dynamics of densovirus infection, their persistence and spread in populations considering their potential use in the regulation of mosquito vector populations.

Extreme temperature event and mass mortality of insectivorous bats - Mathieu Pruvot; Julien Cappelle; Neil Furey; Vibol Hul; Huy Sreang Heng; Veasna Duong; Philippe Dussart; Paul Horwood (European Journal of Wildlife Research, 2019)

The negative ecological impacts of a globally introduced species decrease with time since introduction - Libor Závorka; Mathieu Buoro; Julien Cucherousset (Global Change Biology, 2018)
While there is a long‐history of biological invasions and their ecological impacts have been widely demonstrated across taxa and ecosystems, our knowledge on the temporal dynamic of these impacts remains extremely limited. Using a meta‐analytic approach, we investigated how the ecological impacts of non‐native brown trout ( Salmo trutta ), a model species with a 170‐year‐long and well‐documented history of intentional introductions across the globe, vary with time since introduction. We first observed significant negative ecological impacts immediately after the species introduction. Second, we found that the negative ecological impacts decrease with time since introduction and that the average ecological impacts become nonsignificant more than one century after introduction. This pattern was consistent across other ecological contexts (i.e., geographical location, levels of biological organization, and methodological approach). However, overall negative ecological impacts were more pronounced at the individual and population levels and in experimental studies. While the mechanisms leading to this decrease remain to be determined, our results indicate that rapid response of native organisms (e.g. adaptation, but also local extinction) may play an important role in this dynamic. Changes in native species traits and local extinction can have important conservation implications. Therefore, we argue that the decline of the negative ecological impacts over time should not be used as an argument to neglect the negative impacts of biological invasions.

Analysis of nocturnal air temperature in districts using mobile measurements and a cooling indicator - François Leconte; Julien Bouyer; Rémy Claverie; Mathieu Pétrissans (Theoretical and Applied Climatology, 2017)

The corallimorpharian Paracorynactis hoplites feeds on the sea star Choriaster granulatus in the western Indian ocean - Julien Wickel; Mathieu Pinault; Remi Garnier; Arthur R. Bos (Marine Biodiversity, 2017)

Global Salmonidae introductions reveal stronger ecological effects of changing intraspecific compared to interspecific diversity - Mathieu Buoro; Julian D. Olden; Julien Cucherousset (Ecology Letters, 2016)
The introduction of organisms within the native range of wild conspecifics is a widespread phenomenon and locally modifies patterns in intraspecific diversity. However, our knowledge of the resulting ecological effects, as opposed to those caused by invasion‐induced changes in interspecific diversity, is still limited. Here, we investigated the ecological effects of native and non‐native invaders across levels of biological organisations and recipient organisms using the global and long history introductions of salmonids. Our meta‐analysis demonstrated that the global effects of native species introductions exceeded those induced by non‐native invaders. The impacts of native invaders were primarily manifested at the individual level on wild conspecifics, but remained largely unexplored on other native organisms and at the community and ecosystem levels. Overlooked and poorly appreciated, quantifying the impacts of native invaders has important implications because human‐assisted introductions of domesticated organisms are ubiquitous and likely to proliferate in the future.

Phenological response of a key ecosystem function to biological invasion - Maria Alp; Julien Cucherousset; Mathieu Buoro; Antoine Lecerf (Ecology Letters, 2016)
Although climate warming has been widely demonstrated to induce shifts in the timing of many biological events, the phenological consequences of other prominent global change drivers remain largely unknown. Here, we investigated the effects of biological invasions on the seasonality of leaf litter decomposition, a crucial freshwater ecosystem function. Decomposition rates were quantified in 18 temperate shallow lakes distributed along a gradient of crayfish invasion and a temperature‐based model was constructed to predict yearly patterns of decomposition. We found that, through direct detritus consumption, omnivorous invasive crayfish accelerated decomposition rates up to fivefold in spring, enhancing temperature dependence of the process and shortening the period of major detritus availability in the ecosystem by up to 39 days (95% CI : 15–61). The fact that our estimates are an order of magnitude higher than any previously reported climate‐driven phenological shifts indicates that some powerful drivers of phenological change have been largely overlooked.

Over-sulfated glycosaminoglycans are alternative selectin ligands: insights into molecular interactions and possible role in breast cancer metastasis - Pierre Martinez; Gérard Vergoten; Florent Colomb; Marie Bobowski; Agata Steenackers; Mathieu Carpentier; Fabrice Allain; Philippe Delannoy; Sylvain Julien (Clinical & Experimental Metastasis, 2013)

Climate variability and trends in downscaled high-resolution simulations and projections over Metropolitan France - Robert Vautard; Thomas Noël; Laurent Li; Mathieu Vrac; Eric Martin; Philippe Dandin; Julien Cattiaux; Sylvie Joussaume (Climate Dynamics, 2013)

Estimation of population allele frequencies from next‐generation sequencing data: pool‐versus individual‐based genotyping - Mathieu Gautier; Julien Foucaud; Karim Gharbi; Timothée Cézard; Maxime Galan; Anne Loiseau; Marian Thomson; Pierre Pudlo; Carole Kerdelhué; Arnaud Estoup (Molecular Ecology, 2013)
Molecular markers produced by next‐generation sequencing ( NGS ) technologies are revolutionizing genetic research. However, the costs of analysing large numbers of individual genomes remain prohibitive for most population genetics studies. Here, we present results based on mathematical derivations showing that, under many realistic experimental designs, NGS of DNA pools from diploid individuals allows to estimate the allele frequencies at single nucleotide polymorphisms ( SNP s) with at least the same accuracy as individual‐based analyses, for considerably lower library construction and sequencing efforts. These findings remain true when taking into account the possibility of substantially unequal contributions of each individual to the final pool of sequence reads. We propose the intuitive notion of effective pool size to account for unequal pooling and derive a Bayesian hierarchical model to estimate this parameter directly from the data. We provide a user‐friendly application assessing the accuracy of allele frequency estimation from both pool‐ and individual‐based NGS population data under various sampling, sequencing depth and experimental error designs. We illustrate our findings with theoretical examples and real data sets corresponding to SNP loci obtained using restriction site–associated DNA ( RAD ) sequencing in pool‐ and individual‐based experiments carried out on the same population of the pine processionary moth ( Thaumetopoea pityocampa) . NGS of DNA pools might not be optimal for all types of studies but provides a cost‐effective approach for estimating allele frequencies for very large numbers of SNP s. It thus allows comparison of genome‐wide patterns of genetic variation for large numbers of individuals in multiple populations.

The effect of RAD allele dropout on the estimation of genetic variation within and between populations - Mathieu Gautier; Karim Gharbi; Timothee Cezard; Julien Foucaud; Carole Kerdelhué; Pierre Pudlo; Jean‐Marie Cornuet; Arnaud Estoup (Molecular Ecology, 2013)
Inexpensive short‐read sequencing technologies applied to reduced representation genomes is revolutionizing genetic research, especially population genetics analysis, by allowing the genotyping of massive numbers of single‐nucleotide polymorphisms ( SNP ) for large numbers of individuals and populations. Restriction site–associated DNA ( RAD ) sequencing is a recent technique based on the characterization of genomic regions flanking restriction sites. One of its potential drawbacks is the presence of polymorphism within the restriction site, which makes it impossible to observe the associated SNP allele (i.e. allele dropout, ADO ). To investigate the effect of ADO on genetic variation estimated from RAD markers, we first mathematically derived measures of the effect of ADO on allele frequencies as a function of different parameters within a single population. We then used RAD data sets simulated using a coalescence model to investigate the magnitude of biases induced by ADO on the estimation of expected heterozygosity and F ST under a simple demographic model of divergence between two populations. We found that ADO tends to overestimate genetic variation both within and between populations. Assuming a mutation rate per nucleotide between 10 −9 and 10 −8 , this bias remained low for most studied combinations of divergence time and effective population size, except for large effective population sizes. Averaging F ST values over multiple SNP s, for example, by sliding window analysis, did not correct ADO biases. We briefly discuss possible solutions to filter the most problematic cases of ADO using read coverage to detect markers with a large excess of null alleles.

Recurrent daily rainfall patterns over South Africa and associated dynamics during the core of the austral summer - Julien Crétat; Yves Richard; Benjamin Pohl; Mathieu Rouault; Chris Reason; Nicolas Fauchereau (International Journal of Climatology, 2012)
This paper investigates the influence of some modes of climate variability on the spatio‐temporal rainfall variability over South Africa during the core of the rainy season, December to February (DJF). All analyses are based directly on the rainfall field instead of atmospheric processes and dynamics. An original agglomerative hierarchical clustering approach is used to classify daily rainfall patterns recorded at 5352 stations from DJF 1971 to DJF 1999. Five clusters are retained for analysis. Amongst them, one cluster looks most like the rainfall and circulation mean picture. Another one, representing 37% of the days, describes strong negative rainfall anomalies over South Africa resulting from a regional barotropic trough‐ridge‐trough wave structure and moisture divergence. These dry anomalies are more frequent in El Niño years (with a 0.75 correlation between ENSO and the seasonal occurrences of that cluster) and are associated with a weakening and/or a regional shift of the Walker‐type circulation and the subtropical jet stream. Three clusters, which describe, respectively, a decrease, an increase, and a conservation of the seasonal mean eastward rainfall gradient, are all associated with strong cyclonic moisture flux anomalies centred over Angola or northern Botswana and the anomalous convergence located over the largest positive rainfall anomalies, suggesting the importance of thermal low pressures. One of them is clearly associated with tropical temperate troughs. The rainfall patterns of these three clusters tend to propagate eastward, and their seasonal frequencies tend to increase in La Niña years. Copyright © 2010 Royal Meteorological Society

Usefulness of a genotypic resistance test using dried blood spot specimens in African HIV-infected children with virological failure according to the 2010-revised WHO criteria - Charlotte Charpentier; Jean-Chrysostome Gody; Pascaline Tisserand; Mathieu Matta; Julien Fournier; Olivia Mbitikon; Laurent Bélec (Archives of Virology, 2011)

Perception and Understanding of Invasive Alien Species Issues by Nature Conservation and Horticulture Professionals in Belgium - Sonia Vanderhoeven; Julien Piqueray; Mathieu Halford; Greet Nulens; Jan Vincke; Grégory Mahy (Environmental Management, 2011)

U redox fronts and kaolinisation in basement-hosted unconformity-related U ores of the Athabasca Basin (Canada): late U remobilisation by meteoric fluids - Julien Mercadier; Michel Cuney; Michel Cathelineau; Mathieu Lacorde (Mineralium Deposita, 2011)